Method for designing heat crack / bursting resistance thickness of thin-edge ceramic product

By calculating the critical thickness of thin-edged ceramic products and using crack-resistant mud, the problems of high-end ceramic thin-edged pots are solved due to low strength and heat-resistant explosion, and the high strength and crack resistance of the products are achieved, reducing the transportation and use process risk of damage.

CN119397617APending Publication Date: 2025-02-07JOMOO KITCHEN & BATHROOM
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411428297.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-14
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

High-end ceramic thin-edged basins are prone to damage during transportation and use due to their low strength, large deformation and high incidence of heat explosion. They also require high requirements for the installation environment and the quality of the cabinet, making it difficult to produce and use widely.

Method used

By calculating the critical thickness of thin-edged ceramic products, ensure that the thickness of the cut surface is greater than the critical thickness, and using crack-resistant slurry, including calcined kaolin, quartz, mullite, alumina and other raw materials, optimize the expansion amount and strength to reduce heat resistance, and use Cracking/explosion occurs.

Benefits of technology

Effectively reduce or avoid heat cracking/explosion resistance of thin-edged ceramic products, improve the strength and crack resistance of products, reduce the risk of damage during transportation and use, and make them more suitable for widespread production and use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119397617A_ABST
    Figure CN119397617A_ABST
Patent Text Reader

Abstract

The invention discloses a method for designing the heat crack / bursting resistance thickness of a thin-edge ceramic product, the section thickness of the thin-edge ceramic product is greater than the critical thickness, the critical thickness is equal to (swelling amount / 0.003777) square, and the swelling amount is that the thin-edge ceramic product is heated to a second temperature from a first temperature and is kept for 1 hour; the difference value of the length change of the thin-edge ceramic product after being heated is obtained. The method can avoid or reduce the probability of heat cracking / bursting of the thin-edge ceramic product.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of ceramics, and in particular to a method for designing the heat cracking / explosion resistant thickness of a thin-edge ceramic product. Background Art

[0002] High-end ceramic thin-edge basins have become a beautiful landscape in modern bathroom spaces with their simple and elegant appearance, easy cleaning, excellent materials, exquisite craftsmanship and personalized design. High-end ceramic thin-edge basins have thin edges, large sizes, neatness and beauty, and can be well integrated into various home decoration styles to enhance the overall aesthetics; their countertop area is relatively large, and more items can be placed, with good storage functions, becoming a popular basin in modern home decoration. Therefore, the technical highlights of high-end thin-edge basins are thinness and regularity. The existing thin-edge basin blank strength is about 4.5Mpa.

[0003] Common problems of thin-edge basins include low strength, large deformation, high incidence of heat-resistant cracking, high damage during transportation and handling, and many complaints from peers about the high incidence of cracking after a period of use. Therefore, the previous thin-edge basins had very high requirements for the installation environment and the quality of the cabinets. It was difficult to produce and use them widely, and the production process was very strict. Summary of the invention

[0004] The main purpose of the present invention is to provide a method for designing the heat cracking / explosion resistance thickness of thin-edge ceramic products.

[0005] The technical solution adopted by the present invention to solve its technical problem is:

[0006] A method for designing the heat cracking / explosion resistance thickness of a thin-edge ceramic product, so that the cross-sectional thickness of the thin-edge ceramic product is greater than a critical thickness, where the critical thickness = (expansion amount ÷ 0.003777) square root, and the expansion amount is the difference in length change of the thin-edge ceramic product after being heated at a designed diameter or maximum length after the temperature is raised from a first temperature to a second temperature and maintained for a sufficient time to stabilize the expansion amount.

[0007] Furthermore, in the present invention, the first temperature is 0°C, and the second temperature is 600°C.

[0008] The design diameter or maximum length of the present invention is, for example, if the thin-edge basin is circular with a diameter of 1m, or rectangular with a diagonal of 1m, then the diameter of 1m is the design diameter, or the diagonal of 1m is the maximum length. If it is an irregular shape, then the maximum distance between any two points is the maximum length.

[0009] "Cut thickness" refers to the thickness of the smallest cut surface among all cut surfaces. For example, for a cylinder, the smallest cut surface is the cut surface perpendicular to the axis.

[0010] Furthermore, the sufficient time to maintain the second temperature is preferably 1 to 5 hours.

[0011] Furthermore, the method of the present invention firstly fires a sample of designed diameter or maximum length according to a recipe, tests the expansion of the sample when the temperature is raised from a first temperature to a second temperature and maintained for a sufficient time to stabilize the expansion, and then calculates the critical thickness of the thin-edge ceramic product according to the expansion. When the thickness of the ceramic body section of the thin-edge ceramic product is greater than the critical thickness, the heat cracking / explosion resistance can be reduced or avoided.

[0012] Furthermore, the thickness of the thin-edge ceramic product is the thickness of a portion of the product surface where the temperature difference is large.

[0013] Furthermore, the parts with large temperature difference on the surface of the product include the waterline edge of the side of the basin contacting the hot water and the junction between the bottom and the side of the basin.

[0014] Further, it also includes the use of crack-resistant mud.

[0015] In a preferred embodiment, the crack-resistant mud comprises, by weight:

[0016] 26 to 30 parts of water; 17 to 25 parts of black mud; 10 to 20 parts of calcined kaolin;

[0017] 4 to 15 parts of quartz; 3 to 20 parts of alumina; 1 to 5 parts of mullite; 1 to 5 parts of diopside; 1 to 8.5 parts of material A.

[0018] Furthermore, material A includes, by mass, 15-25 parts of water, 25-32 parts of quartz, 4-7 parts of aluminum oxide, 5-6 parts of calcite, 3-6 parts of dolomite, 3-4 parts of zinc oxide, 10-12 parts of potassium feldspar, and 15-17 parts of sodium feldspar.

[0019] Furthermore, during the preparation of material A, the above raw materials are first put into a ball mill at the same time, and the particle size is controlled to be ≤73-75% of the particles below 10 microns; then the dry weight of the A slurry is calculated, and the materials are added together according to the ratio and then ball-milled, and the overall particle size is controlled to be ≤58-62% of the particles below 10 microns.

[0020] Compared with the background technology, this technical solution has the following advantages:

[0021] 1. Through long-term research, the present invention has obtained a method to reduce the thermal cracking / explosion resistance of thin-edge ceramic products, so that the thickness of thin-edge ceramic products is greater than the critical thickness, which is (expansion amount ÷ 0.003777) square root, and the expansion amount is the difference in the length change of the thin-edge basin material when heated. The size and thickness of the thin-edge basin designed with this formula can solve the problem of thermal cracking / explosion resistance of the basin in the later stage.

[0022] 2. The present invention further develops a mud, which uses calcined kaolin, quartz, mullite, alumina, wollastonite diopside, and ground mixed material A as main raw materials, and sets the expansion amount and strength of the mud under the proportion, thereby solving the problem of easy deformation and cracking of ultra-thin products from the mud. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] The present invention will be further described below in conjunction with the accompanying drawings and embodiments.

[0024] Figure 1 Schematic diagram of the occurrence site of thermal cracking.

[0025] Figure 2 Schematic diagram of the occurrence principle of thermal cracking.

[0026] Figure 3 This is a cross-sectional view of the location where heat cracking occurs.

[0027] Figure 4 Verify the thickness of the part where thermal cracking occurs.

[0028] Figure 5 It is a schematic diagram of the explosion resistance part and the explosion occurrence site.

[0029] Figure 6 This is a graph showing the relationship between expansion and critical thickness.

[0030] Figure 7 This is the autoclave anti-cracking test diagram.

[0031] Figure 8 This is a test of expansion rate, where A is the sample before calcination at 1250°C and B is the sample after calcination.

[0032] Fig. 9 It is an expansion rate tester. DETAILED DESCRIPTION

[0033] The thin-edge products of the present invention include basins, toilets, mop pools, etc. In the following embodiments, a thin-edge basin is used as an example. The shape of the thin-edge basin is as follows: Figure 1 or Figure 2 shown.

[0034] The three major factors that affect the explosion are: Figure 1 and Figure 2 , ① heat stress resistance; ② product strength (crack resistance); ③ thickness

[0035] The pot bursts and the incidence of heat cracking is high. The applicant has calculated a relationship based on a large amount of test data in the early stage: heat cracking occurrence = heat stress > product strength (cracking resistance) ( Figure 1). Thinness and product strength are contradictory points. The applicant uses the principle that different parts of the basin are heated unevenly during heat resistance tests to analyze the relationship between body cracking and strength ( Figure 2 ), design an experiment ( Figure 4 and Figure 5 ), a large number of tests and calculations were conducted to obtain the corresponding relationship between thickness, stress and expansion (among which, some of the applicant's early test data are shown in Tables 1 to 10, and the relationship between the expansion and critical thickness is shown in Figure 6 ), and proposed a critical thickness concept, which can be calculated. Above the critical thickness, the occurrence of thin-edge basin cracks can be avoided. Combined with the newly developed mud formula, the strength (or crack resistance) is improved, and the occurrence of bursting is reduced. The crack resistance test (in an autoclave) and the heat resistance test are both qualified.

[0036] Expansion = 0.003777*1 critical thickness square

[0037] Critical thickness = (expansion amount ÷ 0.003777) square root

[0038] Expansion (increase in linear length due to heating) = expansion rate (%) * length. The expansion rate is related to the mud composition, test body length and temperature.

[0039] Critical thickness = (expansion amount ÷ 0.003777) square root, the expansion amount is the difference in length change of the thin-edge ceramic product after being heated at a designed diameter or maximum length, when the temperature is raised from a first temperature to a second temperature and maintained for a sufficient time to stabilize the expansion amount.

[0040]

[0041]

[0042]

[0043] Then, the expansion amount is reduced through formula optimization, wherein the expansion amount is obtained by measuring the expansion coefficient of 0-600 degrees with a thermal expansion meter.

[0044] Example 1

[0045] In terms of mass parts, water 30; black mud; 25; calcined kaolin 17; quartz 13; calcined alumina 10; mullite 5; diopside 0; A material 0

[0046] Example 2

[0047] In terms of mass parts, water 30; black mud; 25; calcined kaolin 20; quartz 15; calcined alumina 15; mullite

[0048] 1.5; Diopside 5; A material 0

[0049] Example 3

[0050] In terms of mass parts, water 30; black mud; 25; calcined kaolin 20; quartz 15; calcined alumina 15; mullite 1; diopside 1; A material 1

[0051] Example 4

[0052] In terms of mass parts, water 30; black mud; 25; calcined kaolin 20; quartz 15; calcined alumina 10; mullite 1; diopside 1; A material 1.5

[0053] Example 5

[0054] In terms of mass parts, water 30; black mud; 25; calcined kaolin 20; quartz 15; calcined alumina 10; mullite 1; diopside 1; A material 2

[0055] Example 6

[0056] In terms of mass parts, water 30; black mud; 25; calcined kaolin 20; quartz 15; calcined alumina 10; mullite 1; diopside 1; A material 2.5

[0057] Example 7

[0058] In terms of mass parts, water 30; black mud; 25; calcined kaolin 20; quartz 15; calcined alumina 10; mullite 1; diopside 1; A material 8.5

[0059]

[0060]

[0061] Among them, material A: 20 water, 31.5 quartz, 6.3 aluminum oxide, 6 calcite, 6 dolomite, 3.5 zinc oxide, 11.4 potassium feldspar, 15.3 sodium feldspar. First, the raw materials of material A are put into a ball mill for ball milling, and the particle size is controlled to be ≤ 73-75% of particles below 10 microns (measured by a laser particle size analyzer). Then, the dry weight of the material A slurry is calculated, and it is added together with the ball milling according to the ratio of 1% to 9% of the formula, and the overall particle size is controlled to be ≤ 58-62% of particles below 10 microns (measured by a laser particle size analyzer).

[0062] The above examples were used to produce the pots and test bars (both of which were calcined in a tunnel kiln at 1250° C.) to test whether the water absorption rate after calcination and the flexural strength after calcination reached the national standard.

[0063] Expansion rate determination: The slurry of the embodiment is cast into cylindrical test bars and placed in a tunnel kiln for calcination.

[0064] 1. Crack resistance test

[0065] The broken pieces of the calcined basin (specification size ≥ 100mm*100mm) or the slurry of the embodiment are poured into 150mm*150mm square bricks, put into an autoclave, add 2500ml of water, and then control the temperature to 200℃, while increasing the pressure to 1Mpa and keep it for one hour. After cooling, take it out and visually check whether the tile is cracked. Repeat this test twice. If there is no crack, it is qualified.

[0066] 2. Heat resistance test

[0067] Plug the drain of the fired thin-edged basin with a rubber stopper, pour in 80-degree hot water, leave it for 5 minutes, drain the hot water, and it is qualified if there is no cracking.

[0068] 3. Slurry production crack resistance test: inject 150mm*150mm square bricks, put them into the tunnel kiln for calcination, and then put them into the autoclave for crack resistance.

[0069] The expansion rate of the porcelain test strip is measured using a thermal expansion meter, and is based on the value of the unit length change measured at a temperature of 600 degrees, excluding the temperature factor.

[0070] Each embodiment is the expansion rate measured on the thermal expansion meter. Method for measuring the expansion rate after firing: using a thermal expansion meter. Method for making a thermal expansion meter test body: After firing the test bar at 1250 degrees, it is processed into a cylinder with a length of 20mm and a diameter of 5mm (the test body is made in the same way as above), and the expansion rate (%) of the sample from 0 to 600℃ is measured in the thermal expansion meter. The results are shown in the following table.

[0071]

[0072] Calculate the length, expansion amount and critical thickness of each embodiment according to the expansion rate

[0073] Example 1 Length, expansion and critical thickness results

[0074]

[0075]

[0076] Example 2 Length, expansion and critical thickness results

[0077]

[0078]

[0079] Example 7 Length, expansion and critical thickness results

[0080] Straight line length mm Expansion (mm) Critical thickness mm 100 0.0075 1.41 200 0.015 1.99 300 0.0226 2.45 400 0.0311 2.87 500 0.0378 3.16 600 0.0457 3.48 700 0.0526 3.73 800 0.0601 3.99 900 0.0675 4.23 1000 0.0741 4.43

[0081] Verification test:

[0082] Take a basin about one meter long as an example:

[0083] Embodiment 1: The thickness of the basin body is safe when it is above 9.1mm (critical thickness is 9.06mm); basins with thickness below 9mm are cracked in crack resistance test and heat resistance test.

[0084] Example 2: The thickness of the mud basin blank introduced with diopside is safe to be above 8mm (critical thickness 7.93mm). If it is less than 8mm, cracks will be found in crack resistance test and heat resistance test.

[0085] Example 7: The thickness of the basin blank can be reduced to 4.5 mm (critical thickness 4.43 mm). The actual thickness of the basin after firing can reach about 4 mm, which is safe. No cracks occur in the crack resistance test and heat resistance test, which are qualified.

[0086] The above description is only a preferred embodiment of the present invention, and therefore cannot be used to limit the scope of the present invention. That is, equivalent changes and modifications made according to the patent scope of the present invention and the contents of the specification should still fall within the scope of the present invention.

Claims

1. A method for designing the thermal cracking / explosion resistance thickness of thin-edge ceramic products, characterized in that: The cross-sectional thickness of the ceramic body of the thin-edge ceramic product is set to be greater than the critical thickness, where the critical thickness = √(expansion amount ÷ 0.003777), and the expansion amount is the difference in length change of the thin-edge ceramic product after being heated after the temperature is raised from the first temperature to the second temperature and maintained for a sufficient time to stabilize the expansion length.

2. A method for designing the heat cracking / explosion resistance thickness of thin-edge ceramic products according to claim 1, characterized in that: The thickness of the thin-edge ceramic product is the thickness of the portion of the product surface where the temperature difference is large.

3. A method for designing the heat cracking / explosion resistance thickness of thin-edge ceramic products according to claim 2, characterized in that: The parts with large temperature difference on the surface of the product include the waterline edge of the basin side contacting the hot water and the junction between the basin bottom and the side.

4. A method for designing the heat cracking / explosion resistance thickness of thin-edge ceramic products according to claim 1, characterized in that: First, a sample of designed diameter or maximum length is fired according to a recipe, and the sample is tested by heating from a first temperature to a second temperature, and maintaining the temperature for a sufficient time to stabilize the expansion amount, and then the critical thickness of the thin-edge ceramic product is calculated based on the expansion amount.

5. A method for designing the heat cracking / explosion resistance thickness of thin-edge ceramic products according to claim 4, characterized in that: The samples include long strips or thin-edged ceramic products.

6. A method for designing the heat cracking / explosion resistance thickness of thin-edge ceramic products according to claim 4, characterized in that: The sufficient maintaining time is maintaining at the second temperature for 1 hour to 5 hours.

7. A method for designing the heat cracking / explosion resistance thickness of thin-edge ceramic products according to claim 4, characterized in that: The first temperature is 0°C, and the second temperature is 600°C.

8. A method for designing the heat cracking / explosion resistance thickness of thin-edge ceramic products according to any one of claims 1 to 6, characterized in that: It also includes the use of crack-resistant grout.

9. A method for designing the heat cracking / explosion resistance thickness of thin-edge ceramic products according to claim 8, characterized in that: The crack-resistant mud comprises, by weight: 26 to 30 parts of water; 17 to 25 parts of black mud; 10 to 20 parts of calcined kaolin; 4 to 15 parts of quartz; 3 to 20 parts of alumina; 1 to 5 parts of mullite; 1 to 5 parts of diopside; 1 to 8.5 parts of material A.

10. A method for designing the heat cracking / explosion resistance thickness of thin-edge ceramic products according to claim 9, characterized in that: Material A includes, by mass: 15-25 parts of water, 25-32 parts of quartz, 4-7 parts of aluminum oxide, 5-6 parts of calcite, 3-6 parts of dolomite, 3-4 parts of zinc oxide, 10-12 parts of potassium feldspar, and 15-17 parts of sodium feldspar.

11. A method for designing the heat cracking / explosion resistance thickness of thin-edge ceramic products according to claim 10, characterized in that: During the preparation of material A, firstly, all components are put into a ball mill at the same time, and the particle size is controlled to be ≤73-75% of particles below 10 microns; then, the dry weight of the material A slurry is calculated, and the components are added together according to the proportion and ball milled again, and the overall particle size is controlled to be ≤58-62% of particles below 10 microns.